Abiraterone in chemotherapy-naive patients with metastatic castration-resistant prostate cancer: a systematic review of 'real-life' studies. Issue 10 (October 2018) - Marchioni, Michele; Sountoulides, Petros; Bada, Maida; Rapisarda, Sebastiano; De Nunzio, Cosimo; Tamburro, Fabiola Raffaella; Schips, Luigi; Cindolo, Luca
Background: To assess the efficacy and safety of treatment with abiraterone acetate (AA) in chemotherapy-naïve men with metastatic castration-resistant prostate cancer (mCRPC) in the 'real-life' setting. Methods: Data acquisition on the outcomes of the use of AA in chemotherapy-naive patients with mCRPC was performed by a MEDLINE comprehensive systematic literature search using combinations of the following key words: 'prostate cancer', 'metastatic', 'castration resistant', 'abiraterone', 'real life', and excluding controlled clinical trials (phase II and III studies). Identification and selection of the studies was conducted according to the Preferred Reporting Items for Systematic Reviews and Meta-analysis (PRISMA) criteria. Outcomes of interest were overall survival (OS), progression-free survival (PFS), 12-week 50% reduction in prostate-specific antigen (PSA), and grade 3 and higher adverse events. Data were narratively synthesized in light of methodological and clinical heterogeneity. Results: Within the eight identified studies that fulfilled the criteria, a total of 801 patients were included in the meta-analysis. Baseline PSA ranged between 9.5 and 212.0 ng/ml. Most of the patients had bone metastases. Duration of treatment with AA was longer in the studies with lower baseline PSA levels. The median OS ranged between 14 and 36.4 months. The PFS, assessed according to different definitions, ranged from 3.9 to 18.5 months. A 50% PSA reduction at 12 weeks was reached by a variable percentage of patients ranging from 36.0% to 62.1%. Finally, the rate of grade 3 and higher adverse events was reported in three studies and ranged from 4.4% to 15.5%. Conclusions: Despite the high grade of heterogeneity among studies, treatment with AA seems to ensure good survival outcomes in the 'real-life' setting. However, prospective studies based on patients' characteristics being more similar to 'real-life' patients are necessary.